Do Multinational Firms Use Tax Havens to the Detriment of Other Countries? - Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2020)
The use of tax havens by multinational corporations (MNCs) has attracted increasing attention and scrutiny in recent years. This paper provides an exposition of the academic literature on this topic. It begins with an overview of the basic facts regarding MNCs' use of havens, which are consistent with the location of holding companies, intellectual property, and financial activities in havens. However, there is also evidence of significant frictions that limit MNCs' use of havens. These limits can be attributed to nontax frictions (such as the legal and business environment in different jurisdictions), to tax law provisions limiting profit shifting, and to the costs of tax planning. There is evidence consistent with the relevance of each of these channels. The paper also argues that nonhaven countries have available a range of powerful tax law instruments to neutralize the impact of MNCs' use of havens. To the extent that it is not due to political dysfunction, their failure to deploy these instruments more extensively can be viewed as a deliberate policy choice, attributable either to collective action problems among nonhavens or to the possibility that in certain circumstances MNCs' use of havens increases the welfare of nonhaven countries. In either case, MNCs' use of havens is facilitated in crucial respects by the laws of nonhaven countries. Finally, the paper discusses how the distinction commonly drawn in public finance theory between "tax avoidance" and "behavioral responses to taxation" can illuminate current debates about the magnitude and implications of MNCs' profit shifting to havens.
Keywords: H25; F23; 330; multinational firms; tax havens; international taxation; foreign direct investment; CFC rules; thin capitalization rules